Answer:
√10z^3(z - 1)(z + 1).
Step-by-step explanation:
The GCF is √10z* z^2
= √10z^3
So factoring we get
√10z^3(z^2 - 1) The expression in brackets is difference of 2 squares so:
= √10z^3(z - 1)(z + 1)
Answer:
Step-by-step explanation:
plug y into the first equation:
8x+5y=24
8x+5(-4x)=24
8x-20x=24
-12x=24
x=-24/12
x=-2
then plug x to the second equation
y=-4
y=-4(-2)
y=8
x=-2
y=8
<span>B) Cubic Trinomial
It is cubic because it goes up to the 3rd power, as seen in 3x^3. A quadratic function would only go up to the 2nd power, and a quartic function would go to the 4th. It is a trinomial rather than a binomial as it has three terms. The constant is considered as a term. It would be a binomial only if there were two terms.</span>
Answer:
oof
Step-by-step explanation: